Nursing interventions from palliative care in children with acute lymphoblastic leukemia - Cordero Corona, Leticia Yoshoky (2024)
Nursing interventions from palliative care in children with Acute Lymphoblastic Leukemia (ALL) involve multiple activities, favoring the acquisition of the care and human pattern. The objective of this essay is to describe the nursing interventions from palliative care in children with Acute Lymphoblastic Leukemia. Prioritizing the evolutionary process, with the effectiveness of the assistance of human needs; physical, mental, social and spiritual, as well as the preparation of coping with stressful events. The actions that are provided for quality care, favor care with efforts oriented to the reason of carrying out comprehensive management in contexts where circumstances mark a feeling of constant growth to continue attributing to interventions that assist the human right to have palliative care, when the profession of the disease incurs a progression without limitation.